Basic Programming Training Using Scratch for Elementary School Students at SD Negeri 01 Tanah Garam, Solok City - Rizalina Rizalina; Afni Nia Sari; Elvira Sawitri (Universitas Muhammadiyah Jember, 2026)
The rapid development of digital technology has increased the importance of computational thinking skills among elementary school students. However, the introduction of programming at the elementary education level in Indonesia remains limited, especially in schools with restricted access to technology-based learning. This community service activity aimed to improve students' understanding of basic programming concepts through Scratch-based training at SD N 01 Tanah Garam, Solok City. Scratch was selected as a visual programming platform due to its user-friendly interface and suitability for children. The activity employed a participatory training approach, including demonstrations, hands-on practice, mentoring, and project-based learning. Students were introduced to programming concepts such as sequences, loops, and conditional logic through the creation of simple animations and educational games. The implementation results indicated an increase in students’ understanding of basic programming concepts, computational thinking abilities, and enthusiasm for technology learning. Furthermore, teachers gained additional insights into integrating Scratch into classroom learning activities. This activity contributed positively to improving digital literacy and strengthening technology-based learning innovation in elementary schools